Evidence of magnetocaloric effect in (Fe63Ni37)89B11 nanostructured magnetic alloys (2025)
The magnetocaloric effect associated with magnetic entropy changes (ΔSM) and phase transitions in (Fe63Ni37)89B11 (FeNiB) powder alloys was investigated. For this purpose, the particle size of the samples was reduced under milling times of 0 (FNB) and 36 hours (FNB36). X-ray diffraction and Mössbauer spectroscopy results showed the formation of nanostructured magnetic alloys and the coexistence of γ-FCC, α-BCC, and oP-(Fe, Ni)B phases in agreement with the INVAR region. M(H) measurements revealed that both alloys are ferromagnetic soft at room temperature, with coercive field values below ~ 48 Oe. A detailed analysis of the magnetic phase transition using the modified Arrott plot and critical isotherm plots yields critical exponents (β = 0.27, γ = 0.92, and α = 4.4) close to the theoretical exponents obtained from the Tricritical Mean Field model. Moreover, a maximum magnetic entropy change (ΔSM) was evidenced around the phase transition (TC) at ~ 330 K (− ΔSM of 2.58 J kg−1 K−1) for FNB and ~ 415 K (− ΔSM of 0.4 J kg−1 K−1) for FNB36 with an applied field of 1.3 T. The relative cooling power and the temperature-averaged entropy change values were determined, and they exhibited a linear dependency as function of the external field. These findings give a good insight towards the advancements of FNB-based alloys for potential room-temperature magnetic refrigeration technology.